Cerebrospinal fluid neurofilament tracks fMRI correlates of attention at the first attack of multiple sclerosis. (April 2015) - Tortorella, C; Direnzo, V; Taurisano, P; Romano, R; Ruggieri, M; Zoccolella, S; Mastrapasqua, M; Popolizio, T; Blasi, G; Bertolino, A; Trojano, M
Background: Identifying markers of cognitive dysfunction in multiple sclerosis (MS) is extremely challenging since it means supplying potential biomarkers for neuroprotective therapeutic strategies. Objective: The aim of this study is to investigate the relationship between fMRI correlates of attention performance and cerebrospinal fluid (CSF) neurofilament light chain (NFL) levels in patients with clinically isolated syndrome (CIS) suggestive of MS. Methods: Twenty-one untreated, cognitively preserved CIS patients underwent BOLD-fMRI while performing the Variable Attentional Control (VAC) task, a cognitive paradigm requiring increasing levels of attentional control processing. CSF NFL was assessed by ELISA technique. SPM8 random-effects models were used for statistical analyses of fMRI data ( p <0.05 corrected). Results: Repeated-measures ANOVA on imaging data showed an interaction between attentional control load and NFL levels in the right putamen. At the high level of attentional control demand CIS patients with "low NFL levels" showed greater activity in the putamen compared with subjects with "high NFL levels" ( p =0.001). These results are independent of cognitive impairment index. Conclusions: Our findings suggest a relationship between CSF NFL levels and load-dependent failure of putaminal recruitment pattern during sustained attention in CIS and suggest a role of CSF NFL as a marker of subclinical abnormality of cognitive pathway recruitment in CIS.